Bridge Substructure Repairs with Self-Consolidating Concrete and Galvanic Anodes. Issue 27 (December 2018) - Ozyildirim, H. Celik; Sharp, Stephen R.
Historically, the Virginia Department of Transportation (VDOT) has repaired chloride-contaminated reinforced concrete bridge substructure elements that contain vertical and overhead sections with either shotcrete or a conventional A3 (3, 000 psi) or A4 (4, 000 psi) concrete. This study investigated using self-consolidating concrete (SCC), which has a high flow rate, bonds well, has low permeability, and provides smooth surfaces, as another option. The study also explored the use of galvanic anodes to control corrosion activity in SCC repairs. In VDOT's Lynchburg and Staunton Districts, SCC repairs were made with and without the use of galvanic anodes. This provided a means for determining the benefit of using the anodes. The needed repair areas were determined by visual observation and sounding. After 7 years of service, SCC repair areas with and without anodes did not exhibit corrosion activity; small vertical cracks were evident in the SCC but did not affect performance. The anodes can provide protection to the steel immediately adjacent to the repair areas. However, unrepaired concrete areas away from the patched area with anodes now require additional repairs. SCC can be successfully placed; however, attention should be paid to form pressure and slump loss. Selection of repair areas should be based on corrosion-related measurements such as half-cell or chloride content, rather than sounding. Progression of corrosion demonstrates the necessity of removing all chloride-contaminated concrete not just adjacent to, but also away from the reinforcement, as anodes in the repair area will provide protection only in a narrow area around the patch.